Improvements in the Diagnostic Approach for Patients with Suspected Deep Vein Thrombosis or Pulmonary Embolism - Anderson, David R.; Wells, Philip S. (Thrombosis and Haemostasis, 1999)
Deep vein thrombosis (DVT) and pulmonary embolism (PE), collectively known as venous thromboembolism (VTE), are common medical disorders that cause considerable morbidity and may result in fatalities if not promptly diagnosed and appropriately treated.1,2 In recent years there have been several important advances that have improved the diagnostic testing strategies for patients with suspected VTE. First, the accuracy and utility of the clinical diagnosis has been reevaluated and found to be a valuable adjunct to objective testing. Second, the fibrin degradation product, D-dimer, has been shown to be a sensitive and potentially useful test to exclude the diagnosis of VTE. Third, newer imaging modalities, such as spiral computerized tomographic angiography (spiral CT), have become available for the investigation of patients with suspected PE. Finally, diagnostic testing algorithms that rely primarily on non-invasive imaging procedures have been validated for the investigation of patients with suspected DVT and PE.The purpose of this chapter is to update the reader about recent advances and current strategies for the investigation of patients with suspected VTE. As a result of clinical trials, safe and feasible approaches for the management of patients with suspected VTE have been validated that minimize the need for invasive testing and are practical even for small centers with limited radiologic facilities.